THE INFLUENCE OF WORK CULTURE ON EMPLOYEE PERFORMANCE WITH WORK ENVIRONMENT AS A MODERATING VARIABLE - Tobari, Tobari; Purnomo, D; Utami, Eva Yuniarti; Sambodja, Edy; Nurina, Lia (ITB AAS Indonesia Surakarta, 2024)
ABSTRACT This study is a quantitative study with an explanatory approach, namely an approach that uses a number of previous studies as the main reference for finding elements of novelty in the research being carried out. The data used in this study. The result in this article show that each variable used in this article has been successfully proven and can be accepted. This is because the P-Values are positive and below the significance level of 0.05, namely 0.004. In addition, in the next row, the P-Values also tend to be positive and below the significance level of 0.05, namely 0.000. This is because a good Work Culture can increase employee Commitment and Work Spirit which ultimately also has an impact on Employee Performance. Thus, the first and second hypotheses in this article can be accepted. Keywords: Work Culture, Employee Performance, Work Environment